Votive shields from a sanctuary of Aphrodite and Eros (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
This contribution deals with a particular class of materials coming from the sanctuary dedicated to Aphrodite and Eros located on the northern slopes of the Athenian Acropolis. Specifically, reference is made to the discovery of some miniature shields. The interpretative key proposed for these votives is that of gifts made to the divinity during the ritual of passage to adult life. This hypothesis was suggested following the comparison with similar objects found in other contexts, of which an overview is given. This interpretation is conceivable for the sanctuary analyzed since it is already clear that it was connected with rites of passage of status for Athenian girls.
Keywords: Aphrodite; Eros; votive shields; arms; rites of passage